(untitled) (Research, Society and Development, 2023)
The integumentary system refers mainly to the surface that cover the living beings and includes organs such as the skin and structures such as nails, hair, fur, feathers, claws, scales. It is responsible for protection against microorganisms, water loss, radiation; It has thermoregulatory function and secretion of sweat and sebum. However, due to the problems linked to the teaching of comparative anatomy in Brazil, caused by the scarcity of textbooks with a didactic focus and directed towards structures and their physiologies, the learning has become increasingly limited and outdated. Therefore, the objective of this article is to indicate a morphophysiological path for teaching the Integument theme for the discipline of Comparative Anatomy for Biological Sciences, mainly, but which can be used for Veterinary Medicine, Zootechny and Agronomy. In fact, the teaching of the tegument for vertebrates using dissection can provide a didactic advance for the content, starting with the microscopy/structure of the tegument, continuing with the phyla, and, later, the study of more complex and special structures such as glands and appendages.